Lemniscate intestinal loop through an internal hernia after Roux-en-Y gastric bypass cause of coecum mobile. A case report - Demtröder, C. R. D.; Agarius, H.; Le, T. H.; Kirchmeyer, P.; Utz, D.; Giger-Pabst, U.; Dajchin, D. (General Surgery, 2024)
The internal hernia is a typical complication after laparoscopic Roux‑en‑Y gastric bypass surgery. In most cases, there are chronic symptoms that only lead to a diagnostic laparoscopy during the diagnostic exclusion procedure. Less common is acute internal hernia with devastating pain, ileus symptoms and even the development of intestinal gangrene. Although this case describes a typical constellation, it posed a particular challenge because it resulted in mesenteric lemniscate‑like torsion through the Petersen pouch. Case presentation. A 29‑year‑old patient presented to our emergency department with abdominal pain, complained of sudden epigastric pain that lasted overnight, and radiated into the back with a permanent belching every 10 seconds. Four weeks ago, the patient received an abdominoplasty, complaining of postprandial nausea, meterorism and constipation afterwards. 19 months ago, a Roux‑en‑Y gastric bypass with a weight of 109 kg and a body mass index of 42.6 kg/m2 was done. The current body weight was 60 kg and the body mass index was 23.4 kg/m2. After focused assessment with sonography for trauma and the detection of dilated intestinal loops, an abdominal computer tomography (CT) was performed. Radiologically, the suspicion of mesenteric malrotation was confirmed. The SWELL (CT‑graphic swirl sign, excess weight loss >95%, liquid in abdomen CT scan) score was positive with a CT‑graphic swirl sign and an excess weight loss of 108.9% (> 95%), no chylus or ascites. We discussed an immediate, necessary diagnostic laparoscopy. Based on the ileocoecalpol, it was not possible to establish a proper assignment of the detached gastrointestinal tract. The exploration of the sigmoid colon as the only fixed point revealed that this was a complete fixed twisting of the right intestinal part with a twist of the caecum into the right upper abdomen through the Petersen space. This necessitated a laparotomy to manually cancel Bernoulli’s lemniscate‑like loop and perform a mesenteric defect suture of the mesenteric space of Brolin and the Petersen space with a non‑absorbable suture. The intestinal loops and patient recovered quickly. The dismission was on the 4th post‑operative day. Conclusions. The internal hernia after gastric bypass remains a diagnostic challenge despite advances in imaging. Due to the increasing number of patients undergoing bariatric surgery, this differential diagnosis must always be considered in the case of abdominal complaints. In addition to the excess weight loss of >95%, this case shows that a recent abdominoplasty can also provoke an internal hernia.